Deteriorations of pulmonary function, elevated carbon monoxide levels and increased oxidative stress amongst water-pipe smokers - Funda Karaduman Yalcin (International Journal of Occupational Medicine and Environmental Health, 2017)
Objectives: A water pipe (hookah) is a tobacco smoking tool which is thought to be more harmless than a cigarette, and there are no adequate studies about its hazards to health. Water-pipe smoking is threatening health of the youth in the world today. The objective of this study has been to investigate the carbon monoxide (CO) levels in breath, examine the changes in pulmonary function tests (PFT) and to assess the change of the oxidative stress parameters in blood after smoking a water pipe. Material and Methods: This study is a cross-sectional analytical study that has included 50 volunteers who smoke a water pipe and the control group of 50 volunteers who smoke neither a cigarette nor a water pipe. Carbon monoxide levels were measured in the breath and pulmonary function tests (PFTs) were performed before and after smoking a water pipe. Blood samples were taken from either the volunteer control group or water-pipe smokers group after smoking a water pipe for the purpose of evaluation of the parameters of oxidative stress. Results: Carbon monoxide values were measured to be 8.08±7.4 ppm and 28.08±16.5 ppm before and after smoking a water pipe, respectively. This increment was found statistically significant. There were also significant reductions in PFTs after smoking a water pipe. Total oxidative status (TOS), total antioxidant status (TAS) and oxidative stress index (OSI) were found prominently higher after smoking a water pipe for the group of water-pipe smokers than for the control group. Conclusions: This study has shown that water-pipe smoking leads to deterioration in pulmonary function and increases oxidative stress. To the best of our knowledge this study is the only one that has shown the effect of water-pipe smoking on oxidative stress. More studies must be planned to show the side effects of water-pipe habit and protective policies should be planned especially for young people in Europe. Int J Occup Med Environ Health 2017;30(5):731–742